Thermal kinetics of biochar-ethylene vinyl acetate for waste-to-energy: Particle swarm optimization, cloud computing, and artificial intelligence - Wei-Hsin Chen; Che-An Lin; Partha Pratim Biswas; Chih-Chun Chen; Biqing Liang; Sheng-Lun Lin; Hwai Chyuan Ong; Aristotle T. Ubando (Fuel, 2026)

Evolution of swine influenza surveillance and one health governance in Taiwan: from zoonotic risk management to integrated preparedness - Cheng-Han Lin; Tzu-Min Lin; Meng-Wei Lin; Chih-Sheng Lin (Veterinary Research Communications, 2026)

Regional exploitation signals inferred from a data-limited per-recruit assessment of Trichiurus japonicus in Taiwanese waters - Chih-Yu Lin; Yu-Heng Lu; Wen-Qi Xu; Sheng-Ping Wang; Toshihide Kitakado (Regional Studies in Marine Science, 2026)

Particle-Size Control of Radionuclide Enrichment and Environmental Risk Pathways in Slurry from the Wandan Mud Volcano - Chih-Chung Lin; Yu-Sheng Wang; Wei-Hsiang Huang; Ting-Chien Chen; Yuan-Fu Lu (Environmental Pollution, 2026)

Lactate acts as a metabolic brake on inflammation by repressing NLRP3 transcription via NF-κB inhibition - Hsin-An Lin; Hsin-Chung Lin; Chih-Yung Chiou; Hao-Hsuan Peng; Yu-Jen Chen; Bo-Ying Bao; Kuen-Jou Tsai; Chao-Feng Lin; Chieh-Tien Shih; Sheng-I. Hu; Kuo-Yang Huang; Lih-Chyang Chen (Inflammation Research, 2026)

Comparative Online–offline measurement of airborne toxic VOCs for health risk and source identification in an environmental justice community - Hsin-Cheng Hsieh; Yuan-Chang Su; Sheng-Po Chen; Chen-Hsuan Chu; Mei-Hui Tseng; Kuan-Chun Lee; Po-Sheng Tseng; Pei-Hsuan Hsu; Chih-Chung Chang; Chieh-Heng Wang; Jia-Lin Wang (Atmospheric Environment, 2026)

Spatio-temporal dynamics for dolphinfish (Coryphaena hippurus) in the waters around Taiwan: Implications for stock assessment and fisheries management - Wen-Qi Xu; Sheng-Ping Wang; Chih-Yu Lin; Wei-Chuan Chiang; Toshihide Kitakado (Regional Studies in Marine Science, 2026)

Regulated deficit irrigation strategy for greenhouse melons based on water status classification model and crop coefficient–reference evapotranspiration approach - Shih-Lun Fang; Bing-Yun Tsai; Sheng-Chih Chang; Yi-Lung Chang; Min-Hwi Yao; Ming-Kun Chi; Wen-Lin Wang; Bo-Jein Kuo (Irrigation Science, 2026)

Toward sustainable use of dolphinfish (Coryphaena hippurus) in the Northwest Pacific: A framework for stock assessment and management strategy evaluation - Sheng-Ping Wang; Wen-Qi Xu; Chih-Yu Lin; Toshihide Kitakado; Wei-Chuan Chiang (Regional Studies in Marine Science, 2026)

Effects of inflammatory markers and sleep quality in stroke patients by reducing residential PM2.5 levels: A case-crossover intervention study - Wen-Hua Lee; Chen-Ta Lin; Pei-Chih Wu; Sheng-Fu Liang; Cheng-Yu Lin; Yu-Chun Wang; Shih-Chun Candice Lung; Tain-Junn Cheng (Science of The Total Environment, 2026)

Corrigendum to “Cluster-based identification of fishing strategies with robustness assessment: A case study of Taiwanese albacore longline fisheries in the Indian Ocean” [Reg. Stud. Mar. Sci. 93 (2026) 104713] - Sheng-Ping Wang; Sung-Il Lee; Wen-Qi Xu; Chih-Yu Lin; Wen-Pei Tsai; Toshihide Kitakado (Regional Studies in Marine Science, 2026)

Cluster-based identification of fishing strategies with robustness assessment: A case study of Taiwanese albacore longline fisheries in the Indian Ocean - Sheng-Ping Wang; Sung-Il Lee; Wen-Qi Xu; Chih-Yu Lin; Wen-Pei Tsai; Toshihide Kitakado (Regional Studies in Marine Science, 2026)

Evaluating hygroscopic cloud-seeding effects by in-situ observation and real-case simulation - Kai-I Lin; Sheng-Hsiang Wang; Kao-Shen Chung; Pay-Liam Lin; Yu-Chieng Liou; Yi-Hui Chang; Yu-Chih Huang; Lin Yi-Sheng (Atmospheric Research, 2026)

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Protective effects of microalgal macular pigment on diabetic retinopathy upon blue light irradiation induced oxidative stress, inflammation, and MAPK pathways - Meng-Wei Lin; Cheng-Han Lin; Wei-Hong Chiu; Hui-Fang Chang; Wai-Man Cheang; Chien-Chun Chang; Vivian C.H. Wu; Chih-Sheng Lin; Chiu-Mei Kuo (Food Research International, 2025)

Spatiotemporal variations and risks assessment of PAH-bound suspended particles across different Asian countries: Insights from multi-city sampling and source apportionment - Kai Hsien Chi; Yen-Shun Hsu; Sheng-Lun Lin; Charles C.-K Chou; Somporn Chantara; Sereeter Lodoisamba; Thi Tuyet-Hanh Tran; Delgerzul Lodoisamba; Yuan Cheng Hsu; Chih-Da Wu; Tuan Hung Ngo; Shih Yu Pan (Environmental Research, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

An in vivo NanoBiT-based pseudoviral biosensor for real-time monitoring of SARS-CoV-2 spike/hACE2 interactions and therapeutic screening - Cheng-Han Lin; Meng-Wei Lin; Xin-Rui Yang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chin-Hung Tsai; Chih-Sheng Lin (Analytica Chimica Acta, 2025)

Urinary phthalate metabolites associate with blood levels of estrogen quinone-derived hemoglobin adducts in Taiwanese pregnant women - Shu-Li Wang; Dar-Ren Chen; Sheng-Yen Hsu; Chia-Wei Liu; Che Lin; Chien-Wen Sun; Pen-Hua Su; Ying-Chih Tseng; Po-Hsiung Lin (Toxicology Letters, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Integrating satellite information, land use regression, and machine learning to estimate the spatiotemporal variation of ionic composition in PM2.5 across Taiwan - Kang Lo; Tang-Huang Lin; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Chun-Sheng Huang; Ho-Tang Liao; Yee-Lin Wu; Chang-Fu Wu (Science of The Total Environment, 2025)

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

High sensitivity mercury ion detection via thermal shock and quench with molecular sieve-functionalized FETs - Guan-Cheng Zeng; Hsuan-Wei Huang; Chia-Kai Lin; Jung-Chih Chen; Sheng-Chun Hung; Guo-Chun Dong; Yu-Lin Wang (Chemical Engineering Journal, 2025)

Estimating and characterizing spatiotemporal distributions of elemental PM2.5 using an ensemble machine learning approach in Taiwan - Chun-Sheng Huang; Kang Lo; Yee-Lin Wu; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Cheng-Pin Kuo; Ho-Tang Liao; Tang-Huang Lin; Chang-Fu Wu (Atmospheric Pollution Research, 2025)

Corrigendum: Deciphering the influence of dietary synbiotics in white shrimp gut and its effects in regulating immune signaling pathways - Sofia Priyadarsani Das; Zaenal Abidin; Huai-Ting Huang; Yu-Ru Lin; Chih-Yang Huang; Yu-Sheng Wu; Yeh-Fang Hu; Fan-Hua Nan (Frontiers in Marine Science, 2025)

The influence of PM2.5 exposure on SARS-CoV-2 infection via modulating the expression of angiotensin converting enzyme II - Meng-Wei Lin; Cheng-Han Lin; Jia-Rong Chang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chih-Sheng Lin (Journal of Hazardous Materials, 2025)

ZFP36L1 and ZFP36L2 reduce cyclin D1 expression by decreasing expression of E2F1 and long 3’UTR isoform of CCND1 transcripts - Tze-Sian Chan; Kun-Lin Lee; Ching-Sheng Hung; Hsin-Pei Chiang; Chia-Chen Chung; Yu-Chih Liang (Molecular and Cellular Biochemistry, 2025)

SLC10A1 rs2296651 variant (S267F mutation) predicts biochemical traits, hepatitis B virus infection susceptibility and the risk of gallstone disease - Yu-Lin Ko; Wei-Lun Tuan; Ming-Sheng Teng; Wei-Chih Su; Chia‑Chi Wang; Leay-Kiaw Er; Semon Wu; Lung-An Hsu (Molecular Genetics and Genomics, 2024)

Role of HIF-1α-Activated IL-22/IL-22R1/Bmi1 Signaling Modulates the Self-Renewal of Cardiac Stem Cells in Acute Myocardial Ischemia - Wei Lee; Syuan-Ling Lin; Chih-Sheng Chiang; Jui-Yu Chen; Wee-Wei Chieng; Shu-Rou Huang; Ting-Yu Chang; B. Linju Yen; Mien-Chie Hung; Kuan-Cheng Chang; Hsu-Tung Lee; Long-Bin Jeng; et al. (Stem Cell Reviews and Reports, 2024)

Achieving over 42 % indoor efficiency in wide-bandgap perovskite solar cells through optimized interfacial passivation and carrier transport - Zhong-En Shi; Ta-Hung Cheng; Chien-Yu Lung; Chi-Wei Lin; Chih-Lin Wang; Bing-Huang Jiang; Yu-Sheng Hsiao; Chih-Ping Chen (Chemical Engineering Journal, 2024)

Associations among global long interspersed nuclear element-1 DNA methylation, metal exposure, and chronic kidney disease - Yu-Mei Hsueh; Mei-Chieh Chen; Ying-Chin Lin; Chih-Yin Wu; Horng-Sheng Shiue; Sheng-Lun Hsu; Hsi-Hsien Chen; Ya-Li Huang (Archives of Toxicology, 2024)

Enhancing open-circuit voltage and suppression of energy loss in ternary organic photovoltaics utilizing carbazole/bicarbazole-based guest donors - Chun-Yu Lin; Bing-Huang Jiang; Pei-Jui Weng; Yu Hsuan Lin; Yu-Wei Su; Hui-Shan Shih; Zhong-En Shi; Yan-Ru Lin; Jijitha Vailassery; Shih-Sheng Sun; Chih-Ping Chen; Yuan Jay Chang (Chemical Engineering Journal, 2024)

Functional identification of specialized diterpene synthases from Chamaecyparis obtusa and C. obtusa var. formosana to illustrate the putative evolution of diterpene synthases in Cupressaceae - Tsai-Jung Wu; Chi-Chun Lin; Li-Ting Ma; Chih-Kai Yang; Chen-Lung Ho; Sheng-Yang Wang; Fang-Hua Chu (Plant Science, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

Continuous microalgal culture module and method of culturing microalgae containing macular pigment - Meng-Wei Lin; Chih-Sheng Lin; Yu-Tso Chen; Shao-Qian Huang; Yi-Chun Yang; Wen-Xin Zhang; Wei-Hong Chiu; Cheng-Han Lin; Chiu-Mei Kuo (Bioresource Technology, 2024)

Oxidative stress and potential effects of metal nanoparticles: A review of biocompatibility and toxicity concerns - Yung-Li Wang; Yu-Hsuan Lee; Chu-Lin Chou; Yu-Sheng Chang; Wen-Chih Liu; Hui-Wen Chiu (Environmental Pollution, 2024)

Macular pigments produced from microalga Chlorella sp. and applied to alleviate the pathogenic process in diabetic mice - Meng-Wei Lin; Wei-Hong Chiu; Cheng-Han Lin; Dung-Huan Liu; Pei-Ching Wu; Chih-Sheng Lin (Algal Research, 2024)

Emergence of OXA-48-producing hypervirulent Klebsiella pneumoniae strains in Taiwan - Yi-Tsung Lin; Chien Chuang; Sheng-Hua Chou; Chih-Han Juan; Tsuey-Ching Yang; Barry N. Kreiswirth; Liang Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Deciphering the influence of dietary synbiotics in white shrimp gut and its effects in regulating immune signaling pathways - Sofia Priyadarsani Das; Zaenal Abidin; Huai-Ting Huang; Yu-Ru Lin; Chih-Yang Huang; Yu-Sheng Wu; Yeh-Fang Hu; Fan-Hua Nan (Frontiers in Marine Science, 2024)
The health of the host is significantly influenced by the gut microbiota. Penaeus vannamei (white shrimp) is one of the most profitable aquaculture species globally. Synbiotics are typically used as a beneficial diet supplement for raising aquaculture species’ growth capacities and enhancing immunity against pathogenicity. However, the effects of synbiotics on the white shrimp intestinal microbiota remain poorly understood. In the present study, we targeted the V3–V4 region of 16S rRNA genes to analyze the effects of synbiotics on white shrimp gut microbiota. Dietary synbiotics, having Lactobacillus acidophilus , and Moringa oleifera leaf extract were added to the white shrimps’ feed in various proportions in the present study. In total, 490 operational taxonomic units yielding 23 phyla, 41 classes, 94 orders, 151 families, and 250 genera of microorganisms were obtained. The diet containing L. acidophilus at 1 × 10 7 CFU/g and M. oleifera at 2.5 g/kg led to an increase in the relative abundance of beneficial microorganisms through a significant decrease in the α diversity. Moreover, it upregulated several physiological pathways such as carbohydrate metabolism, signal transduction, lipid metabolism, nucleotide metabolism, amino acid metabolism, and environmental adaptation, which led to the upregulation of the AMPK, MAPK, P13K-Akt, lysosome, peroxisome, and ferroptosis signaling pathways; this enhanced growth and immunity in white shrimp. Whether a single species or a combination of different microorganisms improves growth and immunity remains unclear till now. Nevertheless, our results will facilitate further in-depth investigation into beneficial microbial communities for upliftment of white shrimp aquaculture.

Active packaging incorporating chitosan, casein phosphopeptide, and plasmonic modification to maintain quality and regulate the respiration rate of fresh-cut Pyrus serotina Rehder during storage - Chao-Kai Chang; Fang-Yu Lin; Sheng-Yen Tsai; Mohsen Gavahian; Kuan-Chen Cheng; Chih-Yao Hou; Min-Hung Chen; Shella Permatasari Santoso; Chang-Wei Hsieh (Food Packaging and Shelf Life, 2023)

Direct and alternating current electric fields affect pectin esterase and cellulase in tomato (Solanum lycopersicum L.) fruit during storage - Chao-Kai Chang; Sheng-Yen Tsai; Mohsen Gavahian; Kuan-Chen Cheng; Chih-Yao Hou; Bara Yudhistira; Shu-Hui Lin; Shella Permatasari Santoso; Chang-Wei Hsieh (Postharvest Biology and Technology, 2023)

Development of a sampling assembly for PM2.5 CEMS - Shibo Wang; Yu-Mei Kuo; Chih-Wei Lin; Sheng-Hsiu Huang; Chih-Chieh Chen (Journal of Aerosol Science, 2023)

Design and verification of a wearable wireless 64-channel high-resolution EEG acquisition system with wi-fi transmission - Chin-Teng Lin; Yuhling Wang; Sheng-Fu Chen; Kuan-Chih Huang; Lun-De Liao (Medical & Biological Engineering & Computing, 2023)

Integrated ground and vertical measurement techniques to characterize overhead atmosphere: Case studies of local versus transboundary pollution - Chang-Feng Ou-Yang; Chih-Chung Chang; Sheng-Hsiang Wang; Charles C.-K. Chou; Ming-Tung Chuang; Tang-Huang Lin; Wei-Nai Chen; Ta-Chih Hsiao; Ming-Cheng Yen; Yueh-Chen Wang; Neng-Huei Lin; Jia-Lin Wang (Science of The Total Environment, 2023)

HAI-1 is required for the novel role of FGFBP1 in maintenance of cell morphology and F-actin rearrangement in human keratinocytes - Dajun D. Lu; Nanxi Huang; Sheng-Wen A. Li; Jessica R. Fang; Chih-Hsin Lai; Jehng-Kang Wang; Khee-Siang Chan; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2023)

Sources, transport, and visibility impact of ambient submicrometer particle number size distributions in an urban area of central Taiwan - Li-Hao Young; Chih-Sheng Hsu; Ta-Chih Hsiao; Neng-Huei Lin; Si-Chee Tsay; Tang-Huang Lin; Wen-Yinn Lin; Chau-Ren Jung (Science of The Total Environment, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Using cluster algorithms with a machine learning technique and PMF models to quantify local-specific origins of PM2.5 and associated metals in Taiwan - Chin-Yu Hsu; Jhy-Charm Soo; Sheng-Lun Lin; Chih-Da Wu; Kai Hsien Chi; Wen-Chang Hsu; Chun-Chieh Tseng; Yu-Cheng Chen (Environmental Pollution, 2023)

Lightweight Flexible Polyimide-Derived Laser-Induced Graphenes for High-Performance Thermal Management Applications - Yu-Sheng Hsiao; Cai-Wan Chang-Jian; Tzu-Yen Huang; Ying-Lin Chen; Chung-Wei Huang; Jen-Hsien Huang; Nian-Jheng Wu; Shih-Chieh Hsu; Chih-Ping Chen (Chemical Engineering Journal, 2023)

AIoT-Based Ergometer for Physical Training in Frail Elderly with Cognitive Decline: A Pilot Randomized Control Trial - Chih-Chun Lin; Li-Chieh Kuo; Yu-Sheng Lin; Chia-Ming Chang; Fang Wen Hu; Yi-Jing Chen; Chun-Tse Lin; Fong-Chin Su (Journal of Medical and Biological Engineering, 2022)
Purpose Reduced physical activity is reported in the elderly, especially in institutional residents. Institutionalized older adults exhibit a high prevalence of frailty. In this work, we developed an artificial intelligence of things (AIoT)-based feedback assistive strengthening ergometer (AIFASE), for the physical strengthening of the elderly with intelligent assistance. Methods We conducted a 12-week intervention in a long-term care facility. In total, 16 participants (84.38 ± 6.0 years; 4 males and 12 females) were recruited with 1:1 randomization of exercise to control groups. The muscle strength of the lower extremities, timed up and go test (TUG), and Short-form Physical Performance Battery (SPPB) of the participants were measured. The AIFASE system allows the clinical staff to record the personal physical performance of the elderly and generates personalized exercise prescriptions accordingly. AIFASE also displays the current usage status of all ergometers and the users’ physiological conditions. The algorithms were developed to generate warning alerts when the training workload was too large by personal physiological detection. AIFASE automatically customized the exercise prescription according to the user’s exercise performance. Results After a 12-week AIFASE intervention, the intervention group exhibited significant improvements in the strength of the hip flexor, Semi-Tandem Stand, and Tandem Stand. Conclusion In this study, we developed an AIoT ergometer that delivered customized physical training prescriptions to improve the physical performance of long-term care facility residents. We believe that the application of AIFASE will help improve the quality of institutional care.

Physiological Recordings of the Cerebellum in Movement Disorders - Ami Kumar; Chih-Chun Lin; Sheng-Han Kuo; Ming-Kai Pan (The Cerebellum, 2022)
The cerebellum plays an important role in movement disorders, specifically in symptoms of ataxia, tremor, and dystonia. Understanding the physiological signals of the cerebellum contributes to insights into the pathophysiology of these movement disorders and holds promise in advancing therapeutic development. Non-invasive techniques such as electroencephalogram and magnetoencephalogram can record neural signals with high temporal resolution at the millisecond level, which is uniquely suitable to interrogate cerebellar physiology. These techniques have recently been implemented to study cerebellar physiology in healthy subjects as well as individuals with movement disorders. In the present review, we focus on the current understanding of cerebellar physiology using these techniques to study movement disorders.

Cerebellar Oscillations in Familial and Sporadic Essential Tremor - Shi-Bing Wong; Yi-Mei Wang; Chih-Chun Lin; Scott Kun Geng; Nora Vanegas-Arroyave; Seth L. Pullman; Sheng-Han Kuo; Ming-Kai Pan (The Cerebellum, 2022)

L-Theanine Ameliorated Rotenone-Induced Parkinsonism-like Symptoms in Rats - Cheng-Neng Chen; Mao-Hsien Wang; Hung-Sheng Soung; Shu-Mei Chen; Chih-Hsiang Fang; Yi-Wen Lin; Hsiang-Chien Tseng (Neurotoxicity Research, 2022)

Three new species of Cylindrobasidium (Physalacriaceae, Agaricales) from East Asia - Yi-Chung Lin; Chia-Ling Wei; Chi-Yu Chen; Che-Chih Chen; Sheng-Hua Wu (Mycological Progress, 2021)

Naringin Ameliorates Haloperidol-Induced Neurotoxicity and Orofacial Dyskinesia in a Rat Model of Human Tardive Dyskinesia - Mao-Hsien Wang; Chih-Chuan Yang; Hsiang-Chien Tseng; Chih-Hsiang Fang; Yi-Wen Lin; Hung-Sheng Soung (Neurotoxicity Research, 2021)

Molecular Imaging for Radiolabeling a PSMA-Targeted Long Circulating Peptide as a Theranostic Agent in Mice Bearing a Human Prostate Tumor - Ming-Hsin Li; Sheng-Nan Lo; Ming-Wei Chen; Wei-Lin Lo; Yuan-Ruei Huang; Shih-Ying Lee; Su-Jung Chen; Shih-Wei Lo; Shih-Ming Wang; Chih-Hsien Chang (Journal of Medical and Biological Engineering, 2021)

New secondary metabolite with cytotoxicity from spawning soft coral Asterospicularia laurae in Taiwan - Jui-Hsin Su; Chih-I Liu; Mei-Chin Lu; Chi-I Chang; Min-Ying Hsieh; Yu-Chi Lin; Chang-Feng Dai; Ya-Han Zhang; Zheng-Yu Lin; Yun-Sheng Lin (Natural Product Research, 2021)

Shallow gas hydrates off southwest Taiwan and their mechanisms - Yin-Sheng Huang; Shu-Kun Hsu; Chih-Chieh Su; Andrew Tien-Shun Lin; Pai-Sen Yu; Nathalie Babonneau; Gueorgui Ratzov; Serge Lallemand; Pi-Chuen Huang; Shiao-Shan Lin; Jing-Yi Lin; Kuo-Yen Wei; et al. (Marine Geophysical Research, 2021)
We have collected two shallow gas hydrate samples at two sites having different geological settings off southwest Taiwan during the cruise MD214 in 2018. The first core site, MD18-3542, is on the South Yuan-An East Ridge at ~ 1200 m water deep, where a structural unconformity covered by fine-silt sediments appears at ~ 5.5 m below the seafloor. The second core site, MD18-3543, is close to the Good-Weather Ridge at ~ 1100 m water deep, where a gas-related pockmark structure and authigenic carbonates are present at shallow strata with fine-silt sediments near the seafloor. Sediment properties of core MD18-3542 are distinctively different above and below the layer corresponding to the unconformity. Both cores show obvious gaps or voids in the lower core halves. The core features could be linked to the dissociated methane upward migrating from deep strata. Core site settings with upwelling methane would favor the formation of shallow gas hydrates. At site MD18-3542, the shallow hydrate could be formed due to high concentration methane kept beneath the unconformity covered by fine-silt sediments. At site MD18-3543, the shallow hydrate could be formed due to an extremely high flux of upwelling methane trapped either beneath the authigenic carbonates or fine-silt sediments.

The Efficacy and Safety of Transcranial Direct Current Stimulation for Cerebellar Ataxia: a Systematic Review and Meta-Analysis - Tiffany X. Chen; Chen-Ya Yang; Gloria Willson; Chih-Chun Lin; Sheng-Han Kuo (The Cerebellum, 2021)

Correction to: Hispanic Spinocerebellar Ataxia Type 35 (SCA35) with a Novel Frameshift Mutation - Chih-Chun Lin; Shi-Rui Gan; Deepak Gupta; Armin Alaedini; Peter H Green; Sheng-Han Kuo (The Cerebellum, 2021)

Four new species of Phylloporia (Hymenochaetales, Basidiomycota) from southeastern Taiwan - Sheng-Hua Wu; Chiung-Chih Chang; Chia-Ling Wei; Yu-Ting Lin; Siou-Zhen Chen (Mycological Progress, 2020)

Ecological risk assessment of species impacted by fisheries in waters off eastern Taiwan - Chih‐Yu Lin; Sheng‐Ping Wang; Wei‐Chuan Chiang; Shane Griffiths; Hsin‐Ming Yeh (Fisheries Management and Ecology, 2020)
An ecological risk assessment was undertaken using productivity‐susceptibility analysis (PSA) to determine the relative vulnerability of 52 species caught by fisheries in the waters off eastern Taiwan. Overall, eight and 20 species were classified as having high and moderate vulnerability, respectively, and the remaining 24 species were classified as having low vulnerability. The species with the highest vulnerability scores were caught mainly by longline and gillnet fisheries, highlighting the need for improved data collection to facilitate a more detailed investigation using more quantitative methods. The data quality analysis indicated that the quality of data was classified as “moderate” for economically important species. However, many species were considered data‐limited and thus collecting high‐resolution catch and effort information and conducting biological studies, especially relating to age, growth and reproduction, are recommended to improve the reliability of outputs from data‐limited assessments such as PSA.

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Protective Effect of (−)Epigallocatechin-3-gallate on Rotenone-Induced Parkinsonism-like Symptoms in Rats - Hsiang-Chien Tseng; Mao-Hsien Wang; Kuo-Chi Chang; Hung-Sheng Soung; Chih-Hsiang Fang; Yi-Wen Lin; Keng-Yuan Li; Chih-Chuan Yang; Cheng-Chia Tsai (Neurotoxicity Research, 2020)

Hispanic Spinocerebellar Ataxia Type 35 (SCA35) with a Novel Frameshift Mutation - Chih-Chun Lin; Shi-Rui Gan; Deepak Gupta; Armin Alaedini; Peter H Green; Sheng-Han Kuo (The Cerebellum, 2019)

Far-infrared Radiation Improves Motor Dysfunction and Neuropathology in Spinocerebellar Ataxia Type 3 Mice - Shin-Wu Liu; Jui-Chih Chang; Sheng-Fei Chuang; Ko-Hung Liu; Wen-Ling Cheng; Hui-Ju Chang; Huei-Shin Chang; Ta-Tsung Lin; Ching-Liang Hsieh; Wei-Yong Lin; Mingli Hsieh; Shou-Jen Kuo; et al. (The Cerebellum, 2019)

Sodium Metabisulfite: Effects on Ionic Currents and Excitotoxicity - Ming-Chi Lai; Te-Yu Hung; Kao-Min Lin; Pi-Shan Sung; Shyh-Jong Wu; Chih-Sheng Yang; Yi-Jen Wu; Jing-Jane Tsai; Sheng-Nan Wu; Chin-Wei Huang (Neurotoxicity Research, 2018)

Adaptive Weighted Nonlinear Least Squares Method for Fluorodeoxyglucose Positron Emission Tomography Quantification - Sheng-Cheng Huang; Liang-Chih Wu; Wen-Chen Lin; Kang-Ping Lin; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2018)

Mapping and comparative proteomic analysis of the starch biosynthetic pathway in rice by 2D PAGE/MS - Tao-Shan Chang; Chih-Wei Liu; Yu-Ling Lin; Chao-Yi Li; Arthur Z. Wang; Min-Wei Chien; Chang-Sheng Wang; Chien-Chen Lai (Plant Molecular Biology, 2017)

Influence of Thread Design on Dental Implant Osseointegration Assayed Using the Lan-Yu Mini-Pig Model - Shih-Kang Chien; Shui-Sang Hsue; Chih-Shing Lin; Tzong-Fu Kuo; Duen-Jeng Wang; Jen-Chang Yang; Sheng-Yang Lee (Journal of Medical and Biological Engineering, 2017)

Community responses to dam removal in a subtropical mountainous stream - Hao-Yen Chang; Ming-Chih Chiu; Yi-Li Chuang; Chyng-Shyan Tzeng; Mei-Hwa Kuo; Chao-Hsien Yeh; Hsiao-Wen Wang; Sheng-Hai Wu; Wen-Hui Kuan; Shang-Te Tsai; Kwang-Tsao Shao; Hsing-Juh Lin (Aquatic Sciences, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

Rainfall-Runoff Prediction Using Dynamic Typhoon Information and Surface Weather Characteristic Considering Monsoon Effects - Chih-Chiang Wei; Nien-Sheng Hsu; Chien-Lin Huang (Water Resources Management, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Classification of Benign and Malignant Breast Tumors in Ultrasound Images with Posterior Acoustic Shadowing Using Half-Contour Features - Zhuhuang Zhou; Shuicai Wu; King-Jen Chang; Wei-Ren Chen; Yung-Sheng Chen; Wen-Hung Kuo; Chung-Chih Lin; Po-Hsiang Tsui (Journal of Medical and Biological Engineering, 2015)

Human recombinant factor VIIa may improve heat intolerance in mice by attenuating hypothalamic neuronal apoptosis and damage - Chuan-Chih Hsu; Sheng-Hsien Chen; Cheng-Hsien Lin; Ming-Chi Yung (Apoptosis, 2014)

Two-Stage Pumping Control Model for Flood Mitigation in Inundated Urban Drainage Basins - Chih-Chiang Wei; Nien-Sheng Hsu; Chien-Lin Huang (Water Resources Management, 2014)

Exploring a sulfone linker utilizing trimethyl aluminum as a cleavage reagent: solid-phase synthesis of sulfonamides and ureas - Tsai-Wen Chung; Chih-Hau Chen; Chu-Chung Lin; Hsien-Jen Wu; Chung-Ming Sun; Wen-Sheng Chung (Molecular Diversity, 2012)

Using coupled fish behavior–hydrodynamic model to investigate spawning migration of Japanese anchovy, Engraulis japonicus , from the East China Sea to Taiwan - CHEN‐YI TU; YU‐HENG TSENG; TAI‐SHENG CHIU; MAO‐LIN SHEN; CHIH‐HAO HSIEH (Fisheries Oceanography, 2012)
Adult Japanese anchovies ( Engraulis japonicus ) migrate from the East China Sea to the coastal region of Taiwan to spawn around late winter and early spring and, later, their larvae constitute important fisheries in Taiwan. However, their migration route and its mechanism remain unclear. To investigate their spawning migration, we used a coupled fish behavior–hydrodynamic modeling approach. The physical field is simulated by the Pacific Ocean adaptation of the TaIwan Multi‐scale Community Ocean Model (TIMCOM) and the fish migration by Lagrangian tracer tracking with the aid of approximation of fish swimming behavior. We investigated three fish behavioral scenarios: (i) passive tracking of the current, (ii) swimming along with the current, and (iii) swimming along with the current and then changing to swimming toward the optimal spawning temperature. The comparison with and without Changjiang discharge is used to investigate the impacts of discharge reduction due to the Three Gorges Dam. Our results suggest that spawning migration of Japanese anchovy from the East China Sea to Taiwan may be aided by the China Coastal Current and that adult anchovies cannot reach the spawning site by passive advection alone. Thus, the swimming behavior of anchovies is crucial during the spawning migration, as it provides extra velocity and the orientation to the favorable spawning grounds. In addition, the adult anchovy is unlikely to reach the coastal area of Taiwan without Changjiang discharge. Our findings indicate that a coupled fish behavior–hydrodynamic model can help understand the influences of physical environment on the migration of Japanese anchovies.

Identification of furo[3′, 2′:3,4]naphtho[1,2-d]imidazole derivatives as orally active and selective inhibitors of microsomal prostaglandin E2 synthase-1 (mPGES-1) - Chih-Hua Tseng; Cherng-Chyi Tzeng; Pin-Keng Shih; Chia-Ning Yang; You-Chung Chuang; Shin-I Peng; Chang-Sheng Lin; Jih-Pyang Wang; Chih-Mei Cheng; Yeh-Long Chen (Molecular Diversity, 2012)

Electrostatic droplets assisted synthesis of alginate microcapsules - Keng-Shiang Huang; Chih-Hui Yang; Yung-Sheng Lin; Chih-Yu Wang; Kang Lu; Yu-Fan Chang; Yi-Ling Wang (Drug Delivery and Translational Research, 2011)

Molecular characterization of a phenylalanine ammonia-lyase gene (BoPAL1) from Bambusa oldhamii - Lu-Sheng Hsieh; Yi-Lin Hsieh; Chuan-Shan Yeh; Chieh-Yang Cheng; Chien-Chih Yang; Ping-Du Lee (Molecular Biology Reports, 2011)

Alterations in Trace Elements and Oxidative Stress in Uremic Patients with Dementia - Chih-Hung Guo; Wang-Sheng Ko; Pei-Chung Chen; Guoo-Shyng W. Hsu; Chia-Yeh Lin; Chia-Liang Wang (Biological Trace Element Research, 2009)

Active extracts of wild fruiting bodies of Antrodia camphorata (EEAC) induce leukemia HL 60 cells apoptosis partially through histone hypoacetylation and synergistically promote anticancer effect of trichostatin A - Mei-Chin Lu; Ying-Chi Du; Jiunn-Jye Chuu; Shiuh-Lin Hwang; Pao-Chuan Hsieh; Chih-Sheng Hung; Fang-Rong Chang; Yang-Chang Wu (Archives of Toxicology, 2009)

Static Magnetic Fields Promote Osteoblast-Like Cells Differentiation Via Increasing the Membrane Rigidity - Kang-Hsuan Chiu; Keng-Liang Ou; Sheng-Yang Lee; Che-Tong Lin; Wei-Jen Chang; Chang-Chih Chen; Haw-Ming Huang (Annals of Biomedical Engineering, 2007)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)